2007
DOI: 10.1161/01.hyp.0000256764.86208.3d
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical Dimethylarginine Inhibits Shear Stress–Induced Nitric Oxide Release and Dilation and Elicits Superoxide-Mediated Increase in Arteriolar Tone

Abstract: Abstract-L-arginine is the substrate used by NO synthase to produce the vasodilator NO. However, in several human diseases, such as hyperhomocysteinemia, diabetes mellitus, and hypertension, there is an increase in serum levels of methylated L-arginines, such as asymmetrical dimethylarginine (ADMA), which cannot be used by NO synthase to produce NO. Yet, the functional consequence of increased levels of ADMA on the vasomotor function of resistance vessels has not been delineated. We hypothesized that elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
46
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 46 publications
2
46
0
Order By: Relevance
“…Asymmetrical dimethylarginine (ADMA) is a major endogenous inhibitor of vasodilatation by inhibiting the endothelial synthesis of NO, which relaxes vascular smooth muscle. 7,8 In isolated rat arterioles, 9 and likely in small resistance arteries, 10 ADMA inhibits vasodilatation otherwise induced by increased flow/shear stress. Intravenously administered ADMA acutely increases systemic vascular resistance (SVR) and BP in humans and animals.…”
mentioning
confidence: 99%
“…Asymmetrical dimethylarginine (ADMA) is a major endogenous inhibitor of vasodilatation by inhibiting the endothelial synthesis of NO, which relaxes vascular smooth muscle. 7,8 In isolated rat arterioles, 9 and likely in small resistance arteries, 10 ADMA inhibits vasodilatation otherwise induced by increased flow/shear stress. Intravenously administered ADMA acutely increases systemic vascular resistance (SVR) and BP in humans and animals.…”
mentioning
confidence: 99%
“…Superoxide production was increased in human umbilical vein endothelial cells (HUVEC) and isolated arterioles from rat gracilis muscle after incubation with ADMA. [119][120] Moreover, elevated ADMA levels as a result of decreased DDAH activity in lipopolysaccharide (LPS)-treated mice were accompanied by increased production of superoxide which was blocked by treatment with L-NMMA, indicating an uncoupled NOS as the source of superoxide. 121 Evidence from a clinical study in which elevated ADMA levels were correlated with increased NOS-derived production of reactive oxygen species (ROS) in the vasculature of patients undergoing coronary bypass surgery supports this idea; 119 however, definite proof for a causal relationship in diabetes mellitus is still lacking.…”
mentioning
confidence: 99%
“…It has been suggested that increased free fatty acid concentration in obesity may be related to increased levels of asymmetric dimethylarginine (ADMA), an endogenous inhibitor of NO synthase (2). L-Arginine competes with ADMA for the eNOS enzyme (29). Therefore, an increase in NO production after supplementation with L-arginine to obese mice may be due in part to an increase of the arginineto-ADMA ratio in endothelial cells and the reduction of the ADMA inhibitory effect.…”
mentioning
confidence: 99%